2019
DOI: 10.1007/s10620-018-5434-4
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Anti-Tumor Necrosis Factor Therapy of Crohn’s Disease Correlates with Slower Progression of Bowel Damage

Abstract: Introduction-Crohn's disease (CD) follows a relapsing and remitting course incurring cumulative bowel damage over time. The question of whether or not the timing of the initiating biologic therapy affects long-term disease progression remains unanswered. Herein, we calculated rates of change in the Lémann index-which quantifies accumulated bowel damage-as a function of the time between the disease onset and initiation of biologic therapy. We aimed to explore the impact of the earlier introduction of biologics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…However, one study showed that early treatment did not reduce the rate of IBD complications in early versus late/conventional treatment group . Four additional studies showed potential value of early treatment with lower loss of efficacy, decreased time to treatment failure, slower rate of disease progression and improvement in mean HBI scores . A small study showed 91% CR rate in an early treatment group .…”
Section: Resultsmentioning
confidence: 99%
“…However, one study showed that early treatment did not reduce the rate of IBD complications in early versus late/conventional treatment group . Four additional studies showed potential value of early treatment with lower loss of efficacy, decreased time to treatment failure, slower rate of disease progression and improvement in mean HBI scores . A small study showed 91% CR rate in an early treatment group .…”
Section: Resultsmentioning
confidence: 99%
“…There are still few studies in literature focusing on the course of LI following a therapy with biological or immunosuppressive agents. Two recent clinical trials have demonstrated the significant halt of CBD progression in a subgroup of CD patients after 12 months of treatment with an anti-tumor necrosis factor (TNF) drug (p = 0.007 and p = 0.043, respectively) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Lémann index has been used frequently as a valid tool to monitor BD progression [11][12][13]16 . The present study is the rst to investigate the in uence of different medical therapies on the LI score in consecutive patients with early CD, and identi ed predictors for short-term bowel resection.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Earlier use of biological agents tended to slow down the progression of BD. 13 Targeting early CD might be the best way to change the disease course and maximize patient bene t. Unfortunately, patients with CD often experience a delay in diagnosis, which is associated with an increased risk of BD over time. 7,8 The Paris de nition describes early CD as having a disease duration less than or equal to 18 months, without a history of previous treatment using disease-modifying agents (e.g., biologics, immunomodulators).…”
Section: Introductionmentioning
confidence: 99%